Integration of The Form of Sensory Synesthesia in the Memoir Anthology of "Guru Welas Asih" in Biographical Texts Learning - Soleh, Anjas Rusdiyanto; Sabardila, Atiqa; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research aims to identify linguistic forms of changes in the meaning of sensory synesthesia in the anthology of “Guru Welas Asih” memoirs and its use in learning biographical texts in Indonesian language subjects. This research was carried out by applying a descriptive qualitative approach. The data in this research are in the form of words and phrases in the memoir anthology entitled “Guru Welas Asih” by the Memoir Writing Community which contains changes in the meaning of sensory synesthesia. The data source in this research is a memoir entitled “Guru Welas Asih” by the Memoir Writing Community. The memoir consists of 17 titles written by 17 members of the community who work as teachers in various regions in Indonesia. Data collection in this research used listening, note-taking, and documentation techniques. Data analysis in this research uses the agih method by applying advanced techniques in the form of the lesap technique. The results of this research show that in the anthology of “Guru Welas Asih”'s memoirs, there is a linguistic form of change in the meaning of sensory synesthesia in the form of a shift in sensory perception, namely (1) the sense of sight to the sense of touch, (2) the sense of touch to the sense of sight, (3) the sense of sight to the sense of hearing, (4) the sense of hearing to the sense of touch, (5) the sense of hearing to the sense of sight, (6) the sense of taste to the sense of sight, and (7) the sense of touch to the sense of hearing. Apart from that, its use in learning biographical texts can be integrated into the linguistic rules of biographical texts.